1979
DOI: 10.1210/endo-104-4-1000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ouabain on Insulin Release, Adenosine 3',5'-Monophosphate and Guanine 3',5'-Monophosphate in Pancreatic Islets*

Abstract: Isolated pancreatic islets of noninbred ob/ob mice were used to test the hypothesis that adenylate cyclase responds to changes of the transmembrane milieu or electric field in intact beta-cells. In the presence of a phosphodiesterase inhibitor, ouabainstimulated both the release of insulin and the islet content of cAMP. Ouabain had no noticeable effect on the islet content of cGMP. These results support the hypothesis at test. However, because ouabain also had some stimulatory effect on cAMP in islet homogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In the presence of the AC activator forskolin, ouabain further elevated atrial cAMP production. These findings are similar to those that ouabain increases intracellular cAMP production in the intestinal mucosa, pancreatic islets, and brain by stimulating AC [ 13 17 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the presence of the AC activator forskolin, ouabain further elevated atrial cAMP production. These findings are similar to those that ouabain increases intracellular cAMP production in the intestinal mucosa, pancreatic islets, and brain by stimulating AC [ 13 17 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…Such a cAMP rise has been reported in different tissues, including dog renal cortex (53), goldfish intestinal mucosa (2), mouse pancreatic islets (21), murine epithelioid and fibroblastic cell lines (34), rat brain (38), and rat renal collecting tubule cells in culture (28). In each of these reported studies, the concentration of ouabain was likely enough to inhibit Na-K-ATPase to a degree where cytoplasmic sodium increased.…”
Section: Discussionmentioning
confidence: 85%
“…The late stimulatory effect was prominent at low and intermediate glucose, but did not occur at high glucose concentrations. Others have found that at nonstimulatory glucose concentrations ouabain either stimulated insulin release (27)(28)(29)(30)(31) or did not affect it (32,33) and no effects were seen with high glucose concentrations (27,(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%